PENGARUH DISIPLIN KERJA TERHADAP PRESTASI KERJA KARYAWAN (Studi Kasus pada PD Sumber Rezeki 3 Garut) - risan sugiayasin; Muhamad Husen (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This research is motivated by the work performance of employees at PD. Source of Rezeki 3 Garut which tends to decrease. This phenomenon can be caused by various factors, one of which is Work Discipline. The purpose of this study was to determine the effect of work discipline on employee performance at Sumber Rezeki 3 Garut. The method used in this research is descriptive and associative. Quantitative data in this study were obtained through a questionnaire where the data that had been collected was then processed using the SPSS statistical data processing application version 24 For Windows. Based on the analysis and data, information was obtained that the research instrument used in this study was declared valid because it had a value greater than the r table of 0.300 and was declared reliable because it had a Cronbach's alpha value greater than 0.600. From the results of the correlation test, it was found that work discipline has a very strong influence on employee performance with an r value of 0.827 and a coefficient of determination of 63.39% and the remaining 31.60% is influenced by other factors not examined in this study.